VIKTIMISASI STRUKTURAL TERHADAP BURUH MELALUI SISTEM OUTSOURCING - Munir, Abdul (JURNAL SOSIOLOGI, 2014)
This study aims to determine how the structural victimization of workers through an outsourcing system. The study was conducted by using a qualitative approach. Field results showed that the employment relationship through this outsourcing system has presented a balanced treatment that leads to discrimination and exploitation of basic labor rights such outsourcing concerns: overtime pay, basic wages, cost of renewal, social security as well as a ban on joining the union. This is a consequence of incomplete provisions in labor regulations set firmly and definitely involves limiting the field of employment and criminal and administrative penalties to employers in the case violated the actual provisions have been written in the regulation of labor itself. In addition, structural components such as Manpower employment law which actually serve to action surveillance for prevention, did not run due to legal reasons and work priorities. As a result, labor regulations that come with the component structure (disnakertrans) is impressed solely limited to filling completeness of the state administration in the field of labor alone. At that point, the structural victimization of labor outsourcing has occurred.